Pembangunan, Hilangnya Ruang Hidup, dan Gerakan Perempuan Samin di Pegunungan Kendeng Utara, Jawa Tengah - Yusuf Fadli; Salsabila Rahmatullah; Abdul Basit; Sukma Aditya Ramadhan (Research and Development Agency Ministry of Home Affairs, 2026)
The expansion of extractive development has intensified environmental conflicts in many indigenous communities, particularly where economic interests threaten ecological sustainability and local living spaces. The resistance of Samin women in the North Kendeng Mountains, Central Java, represents a significant environmental movement in which women have actively challenged cement industrialization and limestone mining. This study analyzes how Samin women construct ecological resistance by integrating the perspectives of ecofeminism, new social movement theory, and environmental justice. Using a qualitative case study approach, we collected data through in-depth interviews with key actors in the movement, field observations, and document analysis covering government regulations, environmental assessments, legal documents, and media reports. The findings indicate that the Samin women’s movement emerged in response to environmental injustice arising from extractive development that threatened water resources, agricultural livelihoods, and cultural sustainability. Through the philosophy of Ibu Bumi [Mother Earth], women transformed ecological knowledge and cultural values into political agency. Their resistance developed through symbolic actions, legal advocacy, and collective networks involving local communities, civil society organizations, academics, and broader environmental movements. This study argues that the Samin women’s movement is not merely opposition to cement plant development but represents a multidimensional struggle for ecological justice, cultural identity, and the protection of community living spaces.